2021
DOI: 10.1016/j.heliyon.2021.e08570
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression among healthcare workers during COVID-19 pandemic: A cross-sectional study

Abstract: Introduction During a pandemic, healthcare workers (HCWs) are exposed to many stresses that predispose them to psychological disorders. This study aimed to evaluate the impact of the coronavirus disease 2019 (COVID-19) pandemic on the anxiety and depression level of HCWs and determine the relationship between them in terms of their demographic characteristics. Material and Methods This study used a cross-sectional design. The participants consisted of clinical, administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…In this regard, given the key role of nurses in providing high-quality care for COVID-19 patients, attention to their mental health and wellbeing should be a priority for policymakers and health system planners. In addition, appropriate interventions should be performed to improve their psychological condition, particularly in serious pandemic situations (57). Different interventions could be introduced to improve mental health, for example, screening and assessing mental health status, access to mental health care services and early supportive interventions for high-risk nurses, designated rest periods, social support to reduce feelings of isolation, sufficient PPE for nurses to provide protection (58).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, given the key role of nurses in providing high-quality care for COVID-19 patients, attention to their mental health and wellbeing should be a priority for policymakers and health system planners. In addition, appropriate interventions should be performed to improve their psychological condition, particularly in serious pandemic situations (57). Different interventions could be introduced to improve mental health, for example, screening and assessing mental health status, access to mental health care services and early supportive interventions for high-risk nurses, designated rest periods, social support to reduce feelings of isolation, sufficient PPE for nurses to provide protection (58).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found that several risk factors were associated with anxiety including female, younger age 40 years, having a chronic disease, unemployment, status as a student, and frequency of exposure to social media or news that focuses on discussing the pandemic (Xiong et al, 2020). Meanwhile, a study in an urban area in Iran found that female and having a history of exposure to Covid-19 were significantly associated with anxiety experienced by health workers during the Covid-19 pandemic (Motahedi et al, 2021). Another study in Iran found factors associated with anxiety were age and being male (Kamali et al, 2021).…”
Section: Factors Associated With Anxietymentioning
confidence: 99%
“…Each question was answered by one of the following answers: at no time (0), some of the time (1), slightly less than half the time (2), slightly more than half the time (3), most of the time (4), or all the time (5). According to the participants' answers, we categorized them into four categories: no depression (<20), mild depression (20-24), moderate depression (25)(26)(27)(28)(29), or severe depression (≥30) [23]Click or tap here to enter text..…”
Section: Measurementsmentioning
confidence: 99%